How to be a winner ([S. l.] : Nightingale Conant, 1992)
Zig Ziglar's eight-point prescription can help you turn every day into a winning opportunity. You'll learn to stop putting obstacles in your own way and why it's actually easier to succeed than to fail, no matter how challenging the task.
Bibligraphical information is taken from the publisher's catalogue.
Keywords: Achievement motivation; Motivation